Kebiasaan Makanan Ikan Beloso (Saurida undosquamis) di Perairan Laut Cina Selatan Bagian Selatan (LCS) - Moh. Rasyid Ridho; Richardus F. Kaswadji; Indra Jaya; Subhat Nurhakim (Fakultas Biologi | Universitas Jenderal Soedirman, 2005)
The objective of this research is to understand the food habit of the lizard fish (Saurida undosquamis) in Southern South China Sea.For this purpose, purposive random sampling was conducted over 19 stations in trawlable bottom waters using swept area method and sample of 250 of S. undosquamis were examined for their stomach content. The lengths of S. undosquamis under this observation were 15,0-26,8 cm. The result showed that the S. undosquamis is demersal fish that distributed diurnally. The food habit of the S. undosquamis in South China Sea was different between the day and the night. The food habit of S. undosquamis in the day are mainly small demersal fishes, especially Leiognathus leusiscus and Upeneus sulphureus that have the same diurnal distribution pattern as S. undosquamis. Meanwhile, during the night time, the food habit of S. undosquamis was dominated by shrimps.